CALORIC CONTENT OF METAPENAEUS DOBSONI - Vijayaraghavan, Sumitra; Vijayakumaran, M (Indian Journal of Fisheries, 2011)
The caloric content of the entire animal is an important variable to bedetermined in energy flow studies, for its knowledge makes it possible to expressdry weight in terms of energy units. Hence, much effort has been madeearlier to measure the caloric content of the tissues of many organisms (Slobodkinand Richman 1961, Paine and Vadas 1969, Cummins and Wuycheck1971, Snow 1972, Qasim and Jacob 1972, Piatt and Irwin 1973 and Qasimet al 1973). Biochemical constituents of animals are known to vary with seasons,size of the animals, stages of maturity and the availability of food. These inturn aflect the caloric content of the animal. In the present study, an attempthas been made to estimate the caloric content of different size groups of maleand female prawns, Metapenaeus dobsoni using three available methods. Thiswas done to evaluate the extent to which the caloric values of this species varywith size and sex.